Application of the wavelet transform modulus maxima and scale normalization to determine gravity anomalies of adjacent sourses - Chanh, Tin Duong Quoc; Hieu, Dau Duong (Vietnam Journal of Marine Science and Technology, 2019)
Nowadays, the wavelet transform is frequently used in processing and interpretaion of potential field data, to detect accurately the location of the anomaly sources and their properties. For gravity anomalies of adjacent sources, they always superimpose upon each other not only in the spatial domain but also in the frequency domain, making the identification of these sources significantly problematic. In this paper, a new mother wavelet for effective analysis of the locations of the close potential field sources was introduced. By theoretical modeling, using the wavelet transform modulus maxima (WTMM) method, we set up a correlative function between the scale parameter and gravity source depth. Moreover, a scale normalization on the wavelet coefficients was applied to enhance resolution for the separation of these sources in the scalograms, thereby determining their depth. After verifying the reliability of the proposed method on the modeling data, we proposed a process for the location of the gravity anomalies of adjacent sources using the wavelet transform, and then application for analysing some of the gravity profiles in the Mekong Delta. The results of this interpretation were consistent with previously published results, but the level of resolution for this technique was quite coincidental with other methods using different geological data.